Trans-sinus fixation for correction of deviation of the gnathotheca in a hawk (Caracara plancus) - Marchio, Maria Ângela Panelli [UNESP]; Magalhães, Thaís Vendramini [UNESP]; Minto, Bruno Watanabe [UNESP]; Dias, Luís Gustavo Gosuen Gonçalves [UNESP] (Wiley, 2022)
Introduction: For birds of prey, the integrity of the beak is extremely important for defence, hygiene, socialization and especially, feeding. This paper describes successful trans-sinus fixation of a lateral deviation of the mandible in a hawk (Caracara plancus). Case report: The patient was presented with malnutrition and dehydration due to severe left lateral deviation of gnathotheca, with significant malocclusion. Fixation was performed with a 1.0-mm pin and 0.4-mm cerclage, applying contralateral traction to the deviation. The placement of the cerclage enabled full opening of the beak to allow feeding in the postoperative period. At 21 days after surgery, occlusion was perfect and the patient had recovered normal beak function. When clinical follow-up indicated that the bird would be able to survive in the wild, it was released. Conclusion: Trans-sinus fixation was effective in correcting lateral deviation of the gnathotheca in a hawk (C. plancus).
Keywords: beak; gnathotheca; hawk; trans-sinus fixation